Keski-ikäisten naisten koulutustason yhteys itseraportoituun fyysiseen aktiivisuuteen - Puttonen, Marika (2025)
Puttonen, M. 2025. The association between middle-aged women's educational level and self-reported physical activity. Faculty of Sport and Health Sciences, University of Jyväskylä, Master's thesis in Gerontology and Public Health, 69 pages.